Pengaruh Baby Massage terhadap Kualitas Tidur Bayi Usia 0-6 Bulan - Yulanda, Hemawanti Trezza; Novita Eka Kusuma Wardani,; Dina Isfentiani,; Tatarini Ika Pipitcahyani, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Sleep disorders that support the quality of baby's sleep are problems Sleep problems in infants that occur in Indonesia by 44.2%. The purpose of this study was to identify the effect of baby massage on the quality of sleep of infants aged 0-6 months. This research is a type of preexperimental research with a research design of one group pretest posttest. The samples were obtained which were used with purposive sampling techniques as many as 52 babies. The independent variable is baby massage while the dependent variable is the quality sleep of babies aged 0-6 months. Data analysis in this study is univariate and bivariate with Wilcoxon signed rank test. The results stated that there was a change in sleep quality of infants aged 0-6 months after and before baby massage with a significant improvement in sleep quality after treatment, namely p-value 0.000 < α (0.05) which means H0 is rejected and H1 is accepted. It was concluded that there is an influence of baby massage on the quality of sleep of babies aged 0-6 months so that parents can do independently and regularly at home to improve the quality of baby's sleep and sleep quality to be good.